Tomi's Challenges - #2

Geometry Level 3

Let a a and b b be two lengths of an acute triangle, and let α \alpha and β \beta be their opposite angles. If ln ( a ) ln ( b ) = 6 \ln(a)-\ln(b)=-6 , and ln 2 ( sin ( α ) ) + ln 2 ( sin ( β ) ) = 2 \ln^2(\sin(\alpha))+\ln^2(\sin(\beta))=2 , what is ln ( sin ( α ) ) ln ( sin ( β ) ) \ln(\sin(\alpha))\ln(\sin(\beta)) ?


The answer is -17.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tomislav Franov
Apr 16, 2021

The sine theorem is given by: \newline

sin ( α ) a = sin ( β ) b \frac{\sin(\alpha)}{a}=\frac{\sin(\beta)}{b}

\since the angle is acute, we can take the natural log on both sides. After taking the natural log, and transforming the expressions, we get \newline

ln ( sin ( α ) ) ln ( sin ( β ) ) = ln ( a ) ln ( b ) \ln(\sin(\alpha))-\ln(\sin(\beta))=\ln(a)-\ln(b) , that is; \newline ln ( sin ( α ) ) ln ( sin ( β ) ) = 6 \ln(\sin(\alpha))-\ln(\sin(\beta))=-6 .

After squaring both sides, we get \newline

ln 2 ( sin ( α ) ) 2 ln ( sin ( α ) ) ln ( sin ( β ) ) + ln 2 ( sin ( β ) = 36 \ln^2(\sin(\alpha))-2\ln(\sin(\alpha))\ln(\sin(\beta))+\ln^2(\sin(\beta)=36

2 ln ( sin ( α ) ) ln ( sin ( β ) ) = 34 -2\ln(\sin(\alpha))\ln(\sin(\beta))=34

ln ( sin ( α ) ) ln ( sin ( β ) ) = 17 \ln(\sin(\alpha))\ln(\sin(\beta))=-17

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...